Rheological behavior and thermal sensitivity of depectinized passion fruit nectar (Passiflora ligularis) - Marín-Machuca, Olegario; Zambrano-Cabanillas, Abel Walter; Chinchay-Barragán, Carlos Enrique; Perez-Ton, Luis Adolfo; Rojas-Rueda, María del Pilar; Amaranto-Cortez, Carlos Rafael; Vértiz-Osores, Jacinto Joaquín; Marín-Sánchez, Obert (Edelweiss Applied Science and Technology, 2025)
Understanding the thermo-rheological properties of fruit-based beverages is critical for optimizing their industrial processing, stability, and sensory quality. This study evaluates the viscosity and flow behavior of depectinized passion fruit nectar (P. ligularis), standardized to 25° Brix, across a temperature range of 5 to 85°C. Apparent viscosity was measured using a Brookfield DV3T rotational viscometer with concentric cylinder geometry. The nectar displayed Newtonian flow behavior, maintaining consistent viscosity regardless of shear rate. Viscosity decreased significantly with rising temperature, from 0.00778 Pa·s at 5°C to 0.00018 Pa·s at 85°C. The Arrhenius model was applied to describe the temperature dependence of viscosity, yielding an activation energy (Ea) of 38.35 kJ/mol. The model fit was statistically robust (R² = 0.9913; RMSE = 0.000485 Pa·s), indicating predictable thermal behavior. Enzymatic depectinization played a key role in achieving this flow profile, eliminating structural polysaccharides that would otherwise induce non-Newtonian characteristics. These findings are industrially relevant for the design of efficient pasteurization, pumping, and packaging systems, especially for clean-label juice products. By characterizing the thermo-rheological response of this underexplored tropical nectar, this study contributes original data to the field of food engineering and supports the formulation of stable, energy-efficient fruit-based beverages.